The Concept of Adab in Islamic Pedagogy: Bridging Traditional Teachings and Modern Educational Practices - Rifky, Mohammad; Shohib, Muhammad Wildan; Maksum, Muhammad Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The concept of adab in Islamic education plays a pivotal role in shaping the character and moral development of students. Adab, which encompasses ethics, morality, and spiritual values, goes beyond mere social politeness; it integrates character formation with intellectual and spiritual growth. This study explores the application of adab in both traditional and modern Islamic educational practices, emphasizing its significance in fostering a well-rounded individual. In traditional settings, such as pesantren and madrasahs, adab is deeply embedded in the learning process, with teachers serving as role models for both academic and moral values. However, modern education systems, often focused on academic achievement and technical skills, tend to overlook the importance of adab, resulting in a gap in character education. This research identifies the challenges of integrating adab into contemporary education, particularly in the face of technological advancements and the shifting priorities of global education systems. By proposing a more holistic approach, this study suggests that integrating adab into modern curricula can bridge the gap between intellectual competence and moral integrity, fostering individuals who are not only knowledgeable but also ethically responsible. The findings underscore the importance of revisiting adab in Islamic education to create a balanced educational framework that nurtures both the mind and the soul.